The Role of Advertising Expenditure in Measuring Indonesia’s Money Demand Function - Hiew, Lee-Chea; Puah, Chin-Hong; Muzafar Shah, Habibullah (2013)
Using the consumer theory approach as suggested by Habibullah (2009), this study aims to shed new light on monetary authority by incorporating advertising expenditure, a variable that has been neglected in the past, into study of the money demand function in Indonesia. In addition, different measurements of monetary aggregates (simple-sum and Divisia money) have been used in the estimation to provide better insight into the selection of a suitable monetary policy variable for the case of Indonesia. Empirical findings from the error-correction model (ECM) indicate that the advertising expenditure variable has a significant impact on the demand for money. Furthermore, as compared to simple-sum money, the model that used Divisia monetary aggregates rendered more plausible estimation results in the estimation of money demand function.